STRATEGI PEMBELAJARAN AL QUR’AN DI ASRAMA BAIT AL HIKMAH MTs NEGERI SURAKARTA 1 - Mizan, Al; Mustofa, Triono Ali (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
In the present era, the study of the Qur'an is very good to be developed, especially the memorization of the Qur'an, at present many Islamic educational institutions have developed a Qur'an memorization program, one of which is at MTs Negeri 1 Surakarta which has implemented this learning. In a lesson, it will not be separated from the learning strategy, the learning strategy is the most important reference that educators have to support the learning process takes place. In memorizing the Qur'an, each individual has his own way, there are those who only listen to murotal alone and can memorize the Qur'an, and there are also those who by reading repeatedly can memorize, so the point is that memorizing the Qur'an can be done in many ways. The strategy of memorizing the Koran can be said to be successful if the goal of the end of learning is achieved. A good strategy will affect the quality of memorization as well and the teaching and learning process will run effectively and correctly. The purpose of this study is to find the right approach and strategy used for the memorization process of students at MTs Negeri 1 Surakata as well as the steps and evaluation system for learning the Qur'an in the Bait Al-Hikmah Dormitory of MTs N 1 Surakarta. This research method uses descriptive qualitative methods through case studies. This research was conducted at Bait Al-Hikmah Dormitory, MTs Negeri 1 Surakarta in 2023/2024. The main subject of the research.